EDUCATIONAL INNOVATION THROUGH AUDIOVISUAL MEDIA: ENHANCING STUDENT MOTIVATION AND MATHEMATICAL LITERACY - Rivaldo Paul Telussa; Jasmari; Santji Afi Rangkoly; Tut Hidayatillah; Anisah Septiani Bakri (EDUCATIONE, 2025)
The rapid advancement of science and technology has demanded innovation in education, particularly in learning approaches that foster student motivation and engagement. This study aims to investigate the influence of mathematical literacy skills and the use of audiovisual media on student learning motivation at Al-Madina Nabire Middle School. Employing a quantitative method with multiple linear regression analysis, data were collected from 28 eighth-grade students through questionnaires measured on a Likert scale. Classical assumption tests confirmed that the data met requirements for normality, multicollinearity, autocorrelation, and homoscedasticity. The results revealed that mathematical literacy skills did not significantly affect learning motivation, whereas the use of audiovisual media had a significant and positive impact. Simultaneously, both variables accounted for 92% of the variance in learning motivation, with audiovisual media being the dominant factor. These findings suggest that integrating audiovisual media in mathematics education can effectively boost student motivation, offering a more engaging alternative to conventional literacy-focused instruction. This research contributes empirical evidence for educators and policymakers on the benefits of innovative media in learning design, particularly in diverse and challenging school contexts. Future studies are recommended to expand sample size, explore additional variables such as teacher competence or school environment, and apply qualitative methods for deeper insights into the learning process.